Orcaella brevirostris - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
7. Irrawaddy Dolphin Orcaella brevirostris French: Orcelle de |'lrrawaddy / German: Irawadi-Delfin / Spanish: Delfin del Irawadi Other common names: Larger Indian Porpoise, Snubfin Dolphin Taxonomy. Orca brevirostris Owen in Gray, 1866, “Inhab. East coast of India, the harbor of Vizagapatam,” Bay of Bengal. Orcaella brevirostris was split in 2005 by I. Beasley and colleagues into two species, O. brevirostris and O. heinsohni, based on morphological, genetic, and geographic differences; O. heinsohn: was limited to the coastal waters of northern Australia and southern Papua New Guinea. Genetic evidence may also support further differentiation within O. brevirostris, which may warrant new subspecies designations in the future. Nevertheless, this taxonomy has not yet been widely accepted. Monotypic. Distribution. SE Asian coastal waters and river mouths including Bay of Bengal, Ganges Delta, Strait of Malacca, Gulf of Thailand, Sunda Shelf, and Malampaya Sound (Palawan), also in Irrawady (= Ayeyarwady), Mekong, and Mahakam river systems, Chilika and Songkhla lakes. A population that once inhabited Tonle Sap Great Lake in Cambodia has been extirpated. Descriptive notes. Total length up to 280 cm (males) and 210-220 cm (females); weight 115-130 kg. Neonates are c.100 cm in length and weigh 10-12 kg. The Irrawaddy Dolphin has rounded head set on flexible neck, no visible beak, and small dorsalfin (3% of total length) with rounded tip positioned at ¢.60% of the total length along back. Flippers are large and wide, 7-3% of total body length on average, with rounded tips. Shallow groove also runs from neck to dorsal fin along back, a feature that distinguishes the Irrawaddy Dolphin from the closely related Australian Snubfin Dolphin (O. heinsohni). Skin pigmentation ranges from uniform dark gray along most of dorsal surface to paler gray on ventral areas. There are 8-19 pairs of teeth in upper jaw and 11-18 pairs in lower jaw, although teeth may not erupt in some populations. Habitat. Five distinct populations in ...